2018
DOI: 10.1080/15384101.2018.1464845
|View full text |Cite
|
Sign up to set email alerts
|

Seleno-short-chain chitosan induces apoptosis in human breast cancer cells through mitochondrial apoptosis pathway in vitro

Abstract: Seleno-short-chain chitosan (SSCC) was a synthesized chitosan derivative with the molecular weight of 4826.986 Da. The study is aimed to investigate cytotoxicity of SSCC on human breast cancer MCF-7 and BT-20 cells and explore apoptosis-related mechanism in vitro. The MTT (3- [4,5-Dimethylthiazol-2-yl]-2, 5-diphenylterazolium bromide) assay showed that SSCC exhibited significantly cytotoxic effects on MCF-7 and BT-20 cells in a dose- and time-dependent manner, and the effective inhibitory concentration was 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Another important observation we had was that CH-AuNPs did induce changes in the cell cycle of leukemic cells, as we determined previously in HeLa and MCF-710 and as shown in a study done in A549 lung cancer cells treated with CH-AuNPs 35. However, although CH-AuNPs do not induce cell cycle arrest in different cell types, SSCC induced cell cycle arrest in G2 phase in K562 cells34 and in MCF-7 and BT-20 cells 36. These differences could be due to the purity or structure of CH molecule itself, which is different from the AuNPs.…”
Section: Discussionsupporting
confidence: 68%
“…Another important observation we had was that CH-AuNPs did induce changes in the cell cycle of leukemic cells, as we determined previously in HeLa and MCF-710 and as shown in a study done in A549 lung cancer cells treated with CH-AuNPs 35. However, although CH-AuNPs do not induce cell cycle arrest in different cell types, SSCC induced cell cycle arrest in G2 phase in K562 cells34 and in MCF-7 and BT-20 cells 36. These differences could be due to the purity or structure of CH molecule itself, which is different from the AuNPs.…”
Section: Discussionsupporting
confidence: 68%
“…Too many Fas/FasL pathway associated proteins were expressed abnormally in cancer ( Gao et al, 2020 ). Chitosan may regulate the expression of apoptosis associated proteins, subsequently activated the cleavage of caspase-9 and caspase-3, which finally induced apoptosis in mitochondrial pathway ( Wu et al, 2018 ; Wu et al, 2020 ).…”
Section: Chitosan: Source Structure Physicochemical Properties and Ap...mentioning
confidence: 99%
“…[33][34][35] Previous studies have confirmed that caspases and Bcl-2 family proteins, such as Bax and Bcl-2, serve important roles in the mitochondrial apoptotic pathway. [36][37][38] Mortenson et al 39 demonstrated that bortezomib triggered cell apoptosis in small cell lung cancer via decreasing Bcl-2 levels. The results of the present study revealed that nitroxoline markedly decreased the level of Bcl-2, and increased the levels of Bax, cleaved PARP and cleaved caspase-3 in a concentration-dependent manner in H929 and RPMI8226 cells.…”
Section: Discussionmentioning
confidence: 99%